Mesenchymal Stem Cell Isolation from Mice Inguinal Fat Tissue: a protocol to get the best from small samples - Castro-Piedra, Silvia (2019)
Adipose-derived stem cells have great potential for tissue repair because of their multidifferentiation potential, growth factors and cytokines secreted. Currently, there is a vast portion of preclinical and clinical investigations aimed to treat skin wounds, spinal cord injuries and ischemia in the myocardium with promising results. In this study, a small sample of adipose tissue was extracted from mice and the stromal vascular fraction was isolated. Then, it was cultivated in vitro in order to analyze the growth kinetics, expression of stem cell markers and differentiation potential. Stem cells cultivated and expanded from the stromal vascular fraction, showed similar kinetics to that reported in literature. A proportion of analyzed cells showed positivity for the stem cell markers and they were able to differentiate efficiently in adipogenic, chondrogenic and osteogenic lineages. The protocol established in this work allowed to isolate adipose-derived stem cells from a very small sample that met almost all the criteria established by the International Society for Cell and Gene Therapy, giving rise to future research for stablish this tissue as an excellent source of stem cells and the development of alternative therapies to the treatment of wounds.